Phytochemical and Pharmacological Evaluation of Catharanthus pusillus for Antioxidant and Antimicrobial Activity - Yadav, Manjit; Bansal, Mayank (Journal of Biomedical and Pharmaceutical Research, 2024)
The plant Catharanthus pusillus (commonly known as tiny periwinkle) is an underutilized species belonging to the Apocynaceae family. This study investigates the phytochemical composition, antioxidant potential, and antimicrobial efficacy of Catharanthus pusillus extracts, aiming to evaluate its suitability as a source of bioactive compounds. Phytochemical screening revealed the presence of alkaloids, flavonoids, tannins, and phenolic compounds. Antioxidant activity was assessed using DPPH and ABTS radical scavenging assays, and antimicrobial activity was evaluated against a panel of bacterial and fungal pathogens. The findings highlight the plant’s potential as a natural antioxidant and antimicrobial agent. Keywords: Catharanthus pusillus, tiny periwinkle, Terpenoids, DPPH and ABTS, Antimicrobial, Antioxidants